Pengembangan Model Pembelajaran Digital Curation dalam Sistem Informasi PPG Seni Budaya untuk Menata Mengelola dan Mempresentasikan Karya Mahasiswa Secara Terintegrasi - Iriaji; Usep Kustiawan; Titi Rahayuningsih; Ade Richa Daril Janah; Aisha Syauqina Ramadina; Ahmad Sholikin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to develop a Digital Curation learning model in the PPG Information System of Arts and Culture which functions to organize, manage, and present student works in an integrated manner. The main problem raised is the lack of a structured learning system in archiving and exhibiting students' works digitally as part of the reflective and curatorial learning process. This research uses a Research and Development (R&D) approach with the ADDIE model, which focuses on the initial three stages: Analysis, Design, and Development. In the analysis stage, a needs study was carried out through observation, interviews, and analysis of learning documents, which shows the importance of digital curation learning in the context of art. The design stage produces a design of a digital curation-based learning model that includes the flow of curatorial activities, a digital platform for work archives, and learning reflection instruments. In the development stage, an initial prototype of a web-based digital system was developed that allows students to systematically upload, organize, and present works with tagging, cataloging, and multimedia presentation features. The results of the development show that this model has the potential to support students' digital literacy skills, work documentation, and visual communication in an integrative manner.